2021
DOI: 10.1007/s10557-021-07279-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-vitamin K Antagonist Oral Anticoagulants (NOACs) Versus Warfarin in Patients with Atrial Fibrillation Using P-gp and/or CYP450-Interacting Drugs: a Systematic Review and Meta-analysis

Abstract: Purpose: Non-vitamin K antagonist oral anticoagulants (NOACs) are excreted by P-glycoprotein (P-gp) and some are metabolized by CYP450 enzymes such as CYP3A4. Although less drug interactions are present with NOACs, it is unclear whether NOACs should also be preferred over vitamin K antagonists (VKAs) in patients with atrial fibrillation (AF) using pharmacokinetically-interacting drugs. Therefore, the benefit-risk profile of NOACs versus VKAs was investigated in AF patients treated with P-gp and/or CYP450-inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“… 13 14 The findings also align with reports from systematic reviews which included data from both observational studies and subgroup analysis of direct oral anticoagulant (DOAC) trials. 16 However, in a subgroup analysis of the ARISTOTLE trial, specifically comparing apixaban versus warfarin in patients treated with concomitant amiodarone, apixaban was associated with lower rates of major bleeding (HR: 0.61; 95% CI: 0.39 to 0.96). 10 The differences in the findings from our study and the subgroup analysis from the ARISTOTLE trial might be explained by the difference in study design, the diverse definitions of major bleeding implemented by different studies and the larger sample size and the inclusion of real-life non-selected patients in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 14 The findings also align with reports from systematic reviews which included data from both observational studies and subgroup analysis of direct oral anticoagulant (DOAC) trials. 16 However, in a subgroup analysis of the ARISTOTLE trial, specifically comparing apixaban versus warfarin in patients treated with concomitant amiodarone, apixaban was associated with lower rates of major bleeding (HR: 0.61; 95% CI: 0.39 to 0.96). 10 The differences in the findings from our study and the subgroup analysis from the ARISTOTLE trial might be explained by the difference in study design, the diverse definitions of major bleeding implemented by different studies and the larger sample size and the inclusion of real-life non-selected patients in the current study.…”
Section: Discussionmentioning
confidence: 99%
“… 10 In contrast to the current study, earlier studies have reported higher rates of gastrointestinal bleeding with DOACs other than apixaban compared with warfarin. 16 18 19 One possible explanation for this disparity could be the lower sensitivity associated with ICD codes for gastrointestinal bleeding (82.6%) compared with other bleeding outcomes. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Fall prevention is essential, which should include strength, balance and gait training, use of walking aids, correction of environmental hazards, correction of footwear or structural impairments of the feet, vision assessment and treatment, and supplementation of vitamin D and calcium [11] , [31] , [32] , [33] . Likewise, a thorough medication review as part of a comprehensive geriatric assessment [34] should be performed, to switch or discontinue unnecessary, interacting or contraindicated comedication (e.g., fall-risk-increasing drugs) [11] , [30] , [35] , [36] , [37] . Lastly, therapy adherence should be optimized [7] .…”
Section: Discussionmentioning
confidence: 99%
“…They frequently present conflicting advice, varying severity classifications, and significant differences in sensitivity and specificity for detecting DDIs ( Abarca et al, 2006 ; Clauson et al, 2007 ; Vonbach et al, 2008 ; Sweidan et al, 2009 ; Reis and Cassiani, 2010 ; Kongsholm et al, 2015 ; Roblek et al, 2015 ). Understanding the risk associated with DDIs involving oral anticoagulants is of major importance to minimize the risk of hemorrhages or thromboses ( Ufer, 2005 ; Vazquez, 2018 ; Hanigan et al, 2020 ; Li et al, 2020 ; Gronich et al, 2021 ; Holm et al, 2021 ; Grymonprez et al, 2023 ). While several databases list DDIs associated with oral anticoagulants, none specialize exclusively in this category.…”
Section: Introductionmentioning
confidence: 99%